Metode 2M2PR Berbasis Quantum Learning dan Permainan Tradisional dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Biya Ebi Praheto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Language as one of the seven elements of universal culture can not be separated from the culture in its learning. The integration of traditional games is an innovation effort in the process of language learning related to the culture of the nation. Many methods can be developed in learning such as 2M2PR method based on quantum learning and traditional games. Traditional games that can be integrated in language learning such as the ladder snake game and the crank game as well as many more. In this case the teacher must have a creative attitude in selecting and modifying the traditional game so that in accordance with the material to be taught. It is expected that 2M2PR methods and the integration of traditional games in Indonesian language learning can increase the attractiveness in language learning as well as facilitate the subject matter delivered and understood by the students. In addition, with the integration of traditional games can foster a sense of cultural love and introduce the nation's culture to students from an early age.